Sialolipoma of the Floor of the Mouth with Immunohistological Analysis - Ahmed A. Zahrani; Ahmed Qannam; Ra’ed Al Sadhan; Ibrahim O. Bello (Case Reports in Dentistry)
Lipomas are relatively rare in the head and neck, and sialolipoma was described as an entity about 20 years ago as lipoma that entraps salivary gland tissue. Less than 10 cases have been described in the floor of the mouth not related to the major salivary glands. Here, we report a case of sialolipoma affecting the floor of the mouth in a 47-year-old patient and reviewed the clinical, histologic, and immunohistochemical characteristics of the lesion.